Perbandingan massa tanah dengan pupuk organik granul terhadap pertumbuhan dan hasil tanaman brokoli (Brassica oleracea) var. italica kultivar Bejo - Rini Sitawati; Roni Anggara; Sri Nur Widyastuti L (Composite : Jurnal Ilmu Pertanian, 2021)
Broccoli (Brassica oleracea var. italica) which is often called green flower cabbage is one type of vegetable that is popular with the public. To meet the growing needs of broccoli, its cultivation business requires the right planting medium and is rich in nutrients.This study aims to obtain a ratio of soil mass and granule organic fertilizer which can increase the growth and yield of broccoli. The experiment was carried out from March 2017 to May 2017, located in Cicalung Village, Wangunharja Village, Lembang District, West Bandung Regency, with an altitude of 1200 m above sea level. The design used was a randomized block design (RBD) with 7 treatments and repeated 4 times, namely A = 6 kg of soil: 0 kg of granular organic fertilizer, B = 5.9 kg of soil: 0.1 kg of granular organic fertilizer, C = 5, 8 kg soil: 0.2 kg granule organic fertilizer, D = 5.7 kg soil: 0.3 kg granule organic fertilizer, E = 5.6 kg soil: 0.4 kg granule organic fertilizer, F = 5.5 kg soil: 0.5 kg granule organic fertilizer, G = 5.4 kg soil: 0.6 kg granule organic fertilizer.The results showed that in treatment F the use 5.5 kg of soil: 0.5 kg of granular organic fertilizer gave a better effect on plant height, number of leaves, canopy width and gross weight but had the same effect on net weight between treatments give.